Shared Decision-Making (SDM) Toolkit: Train-the-Trainer Tools for Teaching SDM in the Classroom and Clinic - Shawn Mincer; Saint Adeogba; Richard Bransford; Pornsak Chandanabhumma; Michelle Lam; Micheal Lee; Karen Posner; Lynne Robins; Karen Domino (Association of American Medical Colleges, 2013)
Abstract This toolkit is designed for use by attending physicians to teach residents, fellows, medical students, and other healthcare providers and staff how to effectively apply core elements of shared decision-making in clinical encounters with patients regardless of practice setting. Shared decision-making is a two-way strategy to empower the patient to actively make an evidence-based treatment choice with the physician. Incorporating both medical and personal criteria into decisions allows for the deliberation of decisions to include all relevant parties. The toolkit includes self-study materials for trainers, tools for in-situ clinical training for providers, and references for additional resources. Field testing of this training included observation of five providers in the clinic with a total of 16 patients. Observation during training revealed that the most common shared decision-making elements absent from clinical encounters were input from trusted others, patient role, teach back, eliciting preferences, and presenting uncertainties.